2019
DOI: 10.5194/tc-13-1073-2019
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark seasonal prediction skill estimates based on regional indices

Abstract: Abstract. Basic statistical metrics such as autocorrelations and across-region lag correlations of sea ice variations provide benchmarks for the assessments of forecast skill achieved by other methods such as more sophisticated statistical formulations, numerical models, and heuristic approaches. In this study we use observational data to evaluate the contribution of the trend to the skill of persistence-based statistical forecasts of monthly and seasonal ice extent on the pan-Arctic and regional scales. We fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Bonan et al (2019) found evidence for this loss in predictive capacity in GCMs in the Arctic marginal seas between June and May starts by analyzing correlation between sea ice area and sea ice volume from previous months of CMIP5 preindustrial control runs. This springtime "predictability barrier" is also consistent with evaluations of empirical forecasts based on observational data (Walsh et al 2019). Moreover, initialized predictions often perform at substantially lower skill levels than those estimated in potential predictability studies (Guemas et al 2016;Bushuk et al 2019).…”
Section: Introductionsupporting
confidence: 76%
“…Bonan et al (2019) found evidence for this loss in predictive capacity in GCMs in the Arctic marginal seas between June and May starts by analyzing correlation between sea ice area and sea ice volume from previous months of CMIP5 preindustrial control runs. This springtime "predictability barrier" is also consistent with evaluations of empirical forecasts based on observational data (Walsh et al 2019). Moreover, initialized predictions often perform at substantially lower skill levels than those estimated in potential predictability studies (Guemas et al 2016;Bushuk et al 2019).…”
Section: Introductionsupporting
confidence: 76%
“…The study of Brunette et al (2019), which used winter coastal divergence as a predictor of summer Laptev SIE, found maximum skill when coastal divergence was integrated up to the first week of May and a notable drop in skill when integrated to the first week of April. Other statistical prediction systems report skillful detrended SIE predictions for forecasts initialized after 1 May, but not prior to this date, consistent with a spring predictability barrier (Kapsch et al, 2014;Lindsay et al, 2008;Liu et al, 2015;Petty et al, 2017;Schröder et al, 2014;Walsh et al, 2019;Williams et al, 2016;Yuan et al, 2016). Similarly, while not necessarily mentioning a spring barrier, other studies documenting the detrended Arctic SIE prediction skill of dynamical prediction systems display a barrier-like skill structure corresponding to initialization month May (Dirkson et al, 2019;Merryfield et al, 2013;Msadek et al, 2014;Sigmond et al, 2013;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 82%
“…The 5-yr climatology follows a changing climate but does not assume linear change, which may not be warranted, especially if there is a natural variability contribution to Arctic sea ice decline (Swart et al 2015;Zhang 2015;Ding et al 2017). We expect a persistence forecast to be better than the climatological forecast for short lead times based on the observed persistence of sea ice extent anomalies (Walsh et al 2019) and the improvement in short-lead-time forecast skill accompanying improvement in sea ice concentration initialization (Zhang et al 2022). The forecast reverts to climatology over longer time scales by weighting the anomaly persistence contribution to decline exponentially with an MIP anomaly autocorrelation decay time scale determined from observations.…”
Section: Forecast System Mip Calculation and Comparison Forecastsmentioning
confidence: 97%